All the World's Futures- Short Guide : 56th International Art Exhibition- La Biennale di Venezia 2015 (Venice; Marsilio Editori, 2015)
Biennial Short Guide
English
Keywords: N4390-5098 Visual Arts- Exhibitions; Biennial Short Guide; Italy